Residential architecture in the face of changes - Klochko, Asmik (project baikal, 2022)
The ongoing global socio-economic, cultural and political changes give rise to an urgent need for a prudent modernization of traditional models of living environment design. The article is devoted to the problems of the future of post-industrial and post-pandemic residential architecture. The article analyzes the most significant social, economic, political, cultural, technological and other trends in the modern society, which directly affect the architectural design of the living environment. The author reveals the consolidated trends in residential architecture of the near future.